2018
DOI: 10.3390/su10062054
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Energy Sustainable Operations on a Historical Building. The Dante Alighieri High School in Florence

Abstract: Italy has a huge cultural heritage, most of which consists of historical buildings that have changed their original function and use over time. The complex question of building and plant system refurbishment and retrofitting mainly derives from this crucial aspect. The aim of this paper is to provide a simple provisional tool useful for the assessment of efficient, energy sustainable refurbishment solutions for historical buildings and their plant systems. The Dante Alighieri high school (with an important mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 38 publications
(111 reference statements)
0
35
0
1
Order By: Relevance
“…Building-plant system analysis carried out by dynamic simulations using commercial software TRNSYS have been shown in a recent paper [35]. Here [35] the simulation models were calibrated and validated with real data of yearly heating consumption.…”
Section: Dynamic Energy Simulation Of the Building Plant Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…Building-plant system analysis carried out by dynamic simulations using commercial software TRNSYS have been shown in a recent paper [35]. Here [35] the simulation models were calibrated and validated with real data of yearly heating consumption.…”
Section: Dynamic Energy Simulation Of the Building Plant Systemmentioning
confidence: 99%
“…Building-plant system analysis carried out by dynamic simulations using commercial software TRNSYS have been shown in a recent paper [35]. Here [35] the simulation models were calibrated and validated with real data of yearly heating consumption. The authors demonstrated that active operations for plant system improvements can be more effective than building envelope improvements for possible retrofitting and refurbishment projects with minor impact on the historical value of the school building.…”
Section: Dynamic Energy Simulation Of the Building Plant Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…In Italy, the Legislative Decree 102/2014 [13], which implements the European Directive 2012/27/EU, outlines a strategic reference framework specifically aimed at promoting urban renewal projects on public real estate assets in order to improve their energy efficiency [14][15][16][17]. This also with the use of renewable resources present in nature, building systems and technological solutions capable of producing a low environmental impact [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%